CEO social connections and bank systemic risk: The “dark side” of social networks - Adasi Manu, Sylvester; Qi, Yaxuan (Journal of Banking & Finance, 2023)
This paper finds that banks led by socially connected CEOs have a higher degree of systemic risk compared to banks with less socially connected CEOs. To address endogeneity concerns, we employ a difference-in-differences design and the instrumental variable method using CEO death as an exogenous shock to the social network. Our study uncovers two key mechanisms through which CEO social networks impact bank systemic risk. First, banks governed by connected CEOs are more active in interbank transactions. Second, bank pairs featuring connected CEOs display a greater asset similarity in comparison to those without connected CEOs. These findings highlight the significant impact of CEO social connections on banks' interconnectedness and their potential contribution to systemic risk in the banking sector.